2007
DOI: 10.1074/jbc.m702655200
|View full text |Cite
|
Sign up to set email alerts
|

Gβγ-mediated Prostacyclin Production and cAMP-dependent Protein Kinase Activation by Endothelin-1 Promotes Vascular Smooth Muscle Cell Hypertrophy through Inhibition of Glycogen Synthase Kinase-3

Abstract: Endothelin-1 (ET1) is a vasoactive peptide that stimulates hypertrophy of vascular smooth muscle cells (VSMC) through diverse signaling pathways mediated by G q /G i /G 13 heterotrimeric G proteins. We have found that ET1 stimulates the activity of cAMP-dependent protein kinase (PKA) in VSMC as profoundly as the G s -linked ␤-adrenergic agonist, isoproterenol (ISO), but in a transient manner. PKA activation by ET1 was mediated by type-A ET1 receptors (ETA) and recruited an autocrine signaling mechanism distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…ETB receptor stimulation in pulmonary arterial smooth muscle cells reduced agonist-stimulated intracellular cyclic AMP (cAMP) levels, consistent with the negative coupling of ETB receptors to adenyl cyclase [35]. The ETAmediated stimulation of cAMP-dependent protein kinase A activity in vascular smooth muscle cells as profoundly as isoproterenol, resulting in promotion of cell hypertrophy [38]. Conversely, prostacyclin inhibits ET-1 release from endothelial cells [39], and the prostacyclin analogue cicaprost inhibited ET-1 release from human pulmonary arterial smooth muscle cells [40].…”
Section: Discussionmentioning
confidence: 90%
“…ETB receptor stimulation in pulmonary arterial smooth muscle cells reduced agonist-stimulated intracellular cyclic AMP (cAMP) levels, consistent with the negative coupling of ETB receptors to adenyl cyclase [35]. The ETAmediated stimulation of cAMP-dependent protein kinase A activity in vascular smooth muscle cells as profoundly as isoproterenol, resulting in promotion of cell hypertrophy [38]. Conversely, prostacyclin inhibits ET-1 release from endothelial cells [39], and the prostacyclin analogue cicaprost inhibited ET-1 release from human pulmonary arterial smooth muscle cells [40].…”
Section: Discussionmentioning
confidence: 90%
“…We also showed that PKA can be rapidly activated by endothelin-1 or by ATP through cyclooxygenase (COX)-mediated prostanoid synthesis in vascular smooth muscle cells (30,35,37). In addition, the effects of noscapine on the cough reflex may involve opioid sigma receptors (24), although there is no evidence for activation of PKA through these receptors.…”
Section: Ep 2 Prostaglandin Receptors Mediate Regulation Of Myofibrobmentioning
confidence: 96%
“…To examine the role of PKA in the regulation of myofibroblast differentiation by noscapine, we used adenovirus-mediated expression of the PKA inhibitor protein, PKI (Ad-PKI), which we and others have shown to be an effective and specific tool for the assessment of the role of PKA (30,37). As shown in Fig.…”
Section: Noscapine Does Not Affect the Gross Microtubule Content But mentioning
confidence: 99%
“…Given that PKA can phosphorylate GSK-3α, thereby inhibiting the kinase (32,33), this would provide a mechanism for limiting β-adrenergic signaling. Obviously, however, if the inhibition is marked and sustained, serious adverse consequences can result.…”
Section: Figurementioning
confidence: 99%